Phospholipase Cγ1 is required for pre‐TCR signal transduction and pre‐T cell development. Issue 1 (7th November 2016) - Fu, Guoping; Yu, Mei; Chen, Yuhong; Zheng, Yongwei; Zhu, Wen; Newman, Debra K.; Wang, Demin; Wen, Renren
Abstract : Phospholypase C γ1 is important for pre‐TCR mediated Ca2+ mobilization and Erk activation. It is required for cell size increase, cell proliferation, and DN3 to DN4 transition, but not survival of pre‐T cells. Abstract : Pre‐T cell receptor (TCR) signaling is required for pre‐T cell survival, proliferation, and differentiation from the CD4 and CD8 double negative (DN) to the double positive (DP) stage. However, the pre‐TCR signal transduction pathway is not fully understood and the signaling molecules involved have not been completely identified. Phospholipase Cγ (PLCγ) 1 is an important signaling molecule that generates two second messengers, diacylglycerol and inositol 1, 4, 5‐trisphosphate, that are important to mediate PKC activation and intracellular Ca 2+ flux in many signaling pathways. Previously, we have shown that PLCγ1 is important for TCR‐mediated signaling, development and T‐cell activation, but the role of PLCγ1 in pre‐TCR signal transduction and pre‐T cell development is not known. In this study, we demonstrated that PLCγ1 expression level in pre‐T cells was comparable to that in mature T cells. Deletion of PLCγ1 prior to the pre‐TCR signaling stage partially blocked the DN3 to DN4 transition and reduced thymic cellularity. We also demonstrated that deletion of PLCγ1 impaired pre‐T cell proliferation without affecting cell survival. Further study showed that deficiency of PLCγ1 impaired pre‐TCR mediated Ca 2+ flux and Erk activation. Thus our studies demonstrate that PLCγ1 is important for pre‐TCR mediated signal transduction and pre‐T cell development.